Tandem photoelectrochemical cells for solar water splitting. Issue 1 (1st January 2018) - Chen, Qi; Fan, Guozheng; Fu, Hongwei; Li, Zhaosheng; Zou, Zhigang
ABSTRACT: Photoelectrochemical (PEC) water splitting without an external bias is a potential solution to the growing energy crisis because this method can directly convert solar energy into chemical energy. A tandem cell is a frequently used configuration for unassisted overall water splitting because of the advantages that each component are tied together to form a highly efficient integration. A tandem PEC water splitting device is based on different photoelectrode absorbers, and there are two main models including photoanode/photocathode (PEC/PEC) and photoelectrode/photovoltaic (PEC/PV) tandem cells. In this review, we will focus on the concepts, configurations and recent progress of PEC/PEC and PEC/PV cells. Light absorption and energy band matching are the key points to enhance the solar-to-hydrogen (STH) efficiency. Promoting the performance of a standalone semiconductor material and finding new materials, coupled with an optimized configuration, are future steps for the practical application of tandem PEC cells. GRAPHICAL ABSTRACT: Abbreviations: PEC: Photoelectrochemical; STH: Solar-to-hydrogen; PV: Photovoltaic; PV-EL: Photovoltaic-electrolysis; CIGS: Cu(In, Ga)Se2; CGS: CuGa3Se5; ACGSe: (Ag, Cu)GaSe2 ; Co-Ci: Cobalt carbonate; Co-Pi: Cobalt phosphate; cDBR: conductive distributed Bragg reflector; DSC: Dye-sensitized solar cell; IMM: Inverted metamorphic multi-junction; PED: Photoelectrodeposition; S-P: Sputtering + Photoelectrodeposition.